Economic Analysis of Acid Lime Production and Marketing in Nepal: A Benefit-Cost Perspective from Nawalpur East District - Sudip Ghimire; Ujjwal Kumar Rauniyar (Journal of Agriculture and Environment for International Development)
Acid lime plays a crucial role in the livelihoods of many Nepali farmers and holds substantial promise for local economic development. This study analyzed the economic aspects of acid lime production in three municipalities of the Nawalpur East district of Nepal: Madhyabindu, Bulingtar, and Bungdikali, and sought to identify the concerns and potential related to acid lime marketing and manufacturing. Data were gathered from 96 acid lime producers using a semi-structured questionnaire from May 2022 to July 2022. The average areas of acid lime cultivation and productivity were 0.387 ha and 3.061 mt ha-1, respectively. The production cost of acid lime was Rs. 104.82 kg-1. The rental values of land and labor costs (p=0.30) were the highest influencing elements at 35.99% and 19.71%, respectively. Other analyzed factors included the cost of fertilizer (p=0.20), plant protection (p<0.01), Bordeaux-micronutrients (p=0.35), and farm management (p=0.18). Benefit-cost analysis revealed a ratio of 0.80 and mean gross margin of Rs. -19.82 for acid lime production. The major problem for the production of acid lime was the lack of irrigation, whereas the lack of storage was found to be a major market problem and thus needed careful attention from the relevant authorities. This examination indicated that acid lime production is a practical choice for Nepali farmers in the countryside; however, there is a need for improvement in production management. This also suggests that acid lime farming has the potential to become a successful export-focused business in the long run in the Nawalpur East district of Nepal.